Desmopressin acetate nasal spray for adults with nocturia. Issue 12 (2nd December 2017) - Cohn, Joshua A.; Kowalik, Casey G.; Reynolds, W. Stuart; Kaufman, Melissa R.; Milam, Douglas F.; Dmochowski, Roger R.; Wein, Alan J.
ABSTRACT: Introduction : Nocturia impacts 70% of individuals over age 70 years. Nocturnal polyuria is present in up to 88% of adults with nocturia, however, treatment options for reducing nighttime urine production have historically been limited to behavioral modification and off label use of timed diuretics and desmopressin. Noctiva TM (desmopressin acetate nasal spray, DANS, Serenity Pharmaceuticals, LLC) is a novel formulation of desmopressin approved by the Food and Drug Administration for the treatment of nocturia due to nocturnal polyuria in March 2017. Areas covered : Incidence and etiology of nocturia, currently available therapies (approved and off label), and pharmacokinetic, efficacy, and safety data associated with DANS. Expert commentary : DANS has been studied for the treatment of nocturia in adults over age 50 without contraindications to the use of desmopressin. 49% receiving the higher clinical dose experienced ≥50% reduction in nocturnal voids in clinical trials vs. 30% with placebo. Although nadir serum sodium <135 mmol/L was not uncommon (14%), the incidence of sodium ≤125 mmol/L was rare (1%). DANS therefore appears to benefit a significant subset of patients with nocturia while maintaining an acceptable risk profile. Given the risks of hyponatremia, education of patients and prescribers in contraindications and the importance of monitoring are paramount.